The Impact of Innovative Technological Practices for Gifted Children's Education on Support Classroom Teachers' Attitudes and Opinions towards Technology Use - Yıldırım, Pelin; Alan, Burcu; Yıldız, Selin (My University, 2024)
The aim of this study is to determine how innovative practices aimed at meeting the educational needs of gifted children, taught during activities, influence the attitudes and opinions of resource room teachers towards the use of technology in education. This study, conducted with 30 teachers working in the Southeastern and Eastern Anatolia Regions, employed a mixed-methods approach and included various activities such as animations, augmented reality, educational games, and STEAM. Data were collected through the attitude scale and diaries towards the use of technology in education. The results indicate that teachers' attitudes towards technology use did not differ by gender and that innovative applications were beneficial for all teachers. However, deficiencies were observed in teachers' ability to adapt to technologies related to coding, engineering, and STEAM. To address these deficiencies and keep technological knowledge and skills up to date, it is recommended to organize regular professional development programs and seminars.
Keywords: Gifted children; innovative practices; resource room teachers; technology use in education